Pressurized IntraPeritoneal Aerosol Chemotherapy vs. intravenous chemotherapy for unresectable peritoneal metastases secondary to platinum resistant ovarian cancer – study protocol for a randomized control trial - Somashekhar, S. P. (Pleura Peritoneum, 2019)
BACKGROUND: Despite optimal surgery and appropriate first-line chemotherapy, ∼70–80 % of patients with epithelial ovarian cancer will develop disease relapse. The prognosis is poor especially for women with Platinum resistant ovarian cancer. The standard treatment for these groups of patients is non-platinum-containing chemotherapy like taxanes, anthracyclines, gemcitabine, topotecan, and trabectedin. These drugs in various combinations and sequences provide modest survival or symptomatic benefit but with significant side effects. Pressurized IntraPeritoneal Aerosol Chemotherapy (PIPAC) is a minimally-invasive drug-delivery technique specifically addressing limited tissue penetration and poor drug distribution with promising results. PIPAC is a novel method of delivering normothermic chemotherapy into the abdominal cavity as an aerosol under pressure. This concept seems to enhance the effectiveness of intra peritoneal chemotherapy by taking advantage of the physical properties of gas and pressure by generating an artificial pressure gradient and enhancing tissue uptake and distributing drugs homogeneously within the closed and expanded peritoneal cavity. Thus, due to the high local bioavailability during PIPAC, the chemotherapy dosage can be reduced which in turn largely prevents systemic side effects and organ toxicity. METHODS: The study aims to investigate the therapeutic efficacy measured as objective tumour response according to Response Evaluation Criteria in Solid Tumours (RECIST) criteria, of PIPAC in comparison with conventional Intravenous chemotherapy for women with recurrent platinum resistant ovarian cancer with peritoneal metastasis (PM). Consecutive patients diagnosed with PM secondary to platinum-resistant ovarian cancer will be randomized to PIPAC group or IV chemotherapy group. The primary objective of this study is to determine the efficacy after three cycles of PIPAC with cisplatin and doxorubicin in comparison with six cycles of systemic chemotherapy. The secondary outcome measures include morbidity and mortality, overall survival and disease specific survival. Analysis is by intention to treat. AIM: Assess the objective tumour response of PIPAC in comparison with systemic intravenous chemotherapy for women with platinum-resistant ovarian cancer. STUDY TYPE: Prospective randomized control intervention trial. INTERVENTION MODEL: IV Chemotherapy group (Control group) PIPAC group (Experimental group) MASKING: Open label. PRIMARY PURPOSE: Treatment. SAMPLE SIZE: Calculated sample size is 97 and rounded to 100. For each treatment group sample size of 50 will be considered. PRIMARY OUTCOME CRITERIA: Objective tumour response according to Response Evaluation Criteria in Solid Tumours (RECIST) criteria version 1.1. SECONDARY OUTCOME CRITERIA: 1. Morbidity; 2. Disease-specific survival (months between inclusion and death due to ovarian cancer); 3. OS (months between inclusion and death due to any cause); 4. CA 125 levels. DISCUSSION: PIPAC in women with platinum resistant ovarian PM has good response owing to superior tissue penetration and better drug distribution. The procedure is safe and well tolerated owing it to its minimal invasiveness. Typical side-effects of systemic chemotherapy, such as alopecia, peripheral neurotoxicity, nausea and myelosuppression are absent. We expect reduction of ascites with symptomatic relief and CA 125 levels. PIPAC is a novel technique for selected patients with platinum resistant ovarian PM and further investigation in comparative clinical trials with conventional chemotherapy will establish its role as a good palliative treatment option. ETHICS COMMITTEE APPROVAL: Obtained. STATUS: Recruiting. TRIAL REGISTRATION NUMBER: REF/2018/08/021223 Registered on Clinical Trials Registry – India (CTRI); www.ctri.nic.in